2015
DOI: 10.1292/jvms.14-0599
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity and morphological changes of bursal follicles in chickens infected with vaccine or wild-type strains of the infectious bursal disease virus

Abstract: Infectious bursal disease (IBD) is characterized by immunosuppression due to the depletion of lymphocytes in the atrophied bursa of Fabricius (BF). We have sometimes encountered contradictory findings: chickens infected with the vaccine IBD virus (IBDV) strain have sometimes exhibited a highly atrophied BF, but not immunosuppression. In this study, chickens administered vaccine or wild-type strains of IBDV were later vaccinated with the B1 strain of the Newcastle disease virus (NDV). Bursal changes were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Although the morphometric index of the bursa of broilers inoculated with the pathogenic microorganisms (S. typhimurium, C. perfringens and S. typhimurium + C. perfringens) did not indicate immunosuppression, the histopathological analysis of the organs revealed signs of atrophy at day 22; changes in the integrity as well as in the function of the bursa can cause changes in the production of immunoglobulins [33] which implies immunosuppression. These results indicate that macroscopic evaluation of the bursa does not always reflect the immune capacity or damage degree of the bursa [30]. It should be noted that no signs of atrophy were found in the histopathological analysis of the synbiotic group, which is consistent with the morphometric index (equal to or greater than 1.1) found in that group.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although the morphometric index of the bursa of broilers inoculated with the pathogenic microorganisms (S. typhimurium, C. perfringens and S. typhimurium + C. perfringens) did not indicate immunosuppression, the histopathological analysis of the organs revealed signs of atrophy at day 22; changes in the integrity as well as in the function of the bursa can cause changes in the production of immunoglobulins [33] which implies immunosuppression. These results indicate that macroscopic evaluation of the bursa does not always reflect the immune capacity or damage degree of the bursa [30]. It should be noted that no signs of atrophy were found in the histopathological analysis of the synbiotic group, which is consistent with the morphometric index (equal to or greater than 1.1) found in that group.…”
Section: Discussionsupporting
confidence: 75%
“…According to the anatomic-physiological development of the bursa of Fabricius in normal conditions and free of stress, it is expected that this organ maintains a sustained growth until broilers reach eight weeks of life, where it will naturally begin the process of atrophy. Several authors have reported moderate atrophy of the bursa towards the sixth or seventh week in birds subjected to different challenges such as bedding reuse, Gumboro disease infection [30,31], immobilization, turning [19], heat stress [32] and overcrowding [33]. Decreased bursa weight is known to be associated with immunosuppression, Gomes et al, [33] found that by decreasing bursa weight, broilers are more susceptible to enteritis caused by Salmonella enterica subsp.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the percentage of larger lymphoid follicles in the BF decreased after chicken infection with aIBDV, suggesting the occurrence of damage, such as bursal atrophy and dehydration, in aIBDV-infected chickens. This damage is considered a pathological change resulting from IBDV infection ( Aihara et al, 2015 ; Huang et al, 2021 ). Moreover, a study demonstrated that ghrelin mitigated bursal fibrosis in SPF chicks infected with IBDV by reducing the number of inflammatory cells and downregulating the expression of TGF-β and MMP-9 ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each bursa was then cut in two parts: a first half was placed in a 10%-formalin solution (10 samples per date, one tube per sample) for histopathological analysis. The formalin-fixed specimens of bursa were embedded in paraffin, sectioned (4 µm thick) and stained with hematoxylin and eosin according to the method described by Aihara et al [18]. The stage of the lesions indicative of IBDV replication in the bursa was read and classified under light microscopic examination.…”
Section: Bbr = Bursa Weight (G) / Body Weight (G) X 100mentioning
confidence: 99%